ANALYSIS OF SOURCES OF FUNDS FOR INDONESIAN ISLAMIC BANKS - Zulkifli Hasibuan, Mhd; Siregar, Saparuddin; Sugianto, Sugianto (CV. Radja Publika, 2022)
Islamic banks are banks that carry out business activities based on sharia principles, or Islamic legal principles regulated in the fatwa of the Indonesian Ulema Council such as the principles of justice and balance ('adl wa tawazun), benefit (maslahah), universalism (natural ), and do not contain gharar, maysir, usury, injustice and unlawful objects. Funds can also be obtained from own capital, namely by issuing or selling shares. Acquisition of funds is also adjusted to the purpose of the use of these funds. The selection of funding sources will determine the size of the costs borne. Therefore, the selection of sources of funds must be done properly. If the purpose of obtaining funds is for daily activities, the source is clearly different from if the bank wants to make a new investment or to expand a business. Funds needed for the bank's main activities are obtained in various deposits, whereas if the funds needed are used for new investments or business expansion, they are obtained from own capital.